The Emergence of Knowmads from the Knowledge Workers - Iliescu Andra Nicoleta (Management Dynamics in the Knowledge Economy, 2021)
The purpose of this paper is to contribute to the academic advances in the knowledge management field, by increasing the understanding of the knowmad workforce. Knowledge economy represents the context in which organizations and individuals strive to learn continuously, to remain competitive, and to reach success. In this context, knowledge management joins other management specializations in the dedicated quest of optimizing organizational knowledge dynamics. Over the past decades, in close connection with unpredictable developments in all facets of our lives, which impact the business environment as well, a new typology of workers is being recognized in the knowledge management literature. The knowmads are emerging from the knowledge workers in a context of an intensified knowledge economy and they are developing skills and competencies that are suitable for the global markets, becoming autonomous, innovative, highly adaptable, and entrepreneurial members of the organizations, as this study proves. The research objective of this paper is to find and analyze the core conditions that favor the emergence of the knowmads from the knowledge workers. Through extensive literature review and by using data analysis software, key concepts are identified in close relation with knowmads. In the first part the intensification of the knowledge economy in Society 3.0 is analyzed from a critical perspective while, in the second part, the significant skills and competencies shift is being discussed. The working hypothesis of this research is that knowmads represent a new type of knowledge worker. Therefore, a comparison between the two worker groups from a skill, competencies, and attributes perspective was also implemented for increased methodological coherence. As this paper shows, in the intensified and global knowledge economy environment and under the forces of digitalization, technologization, new key competencies become essential within organizations. The holders of these competencies prove to be the knowmads, the new workers’ group emerging from the knowledge workers in the late 21st century.